KAJIAN MUSIKOLOGI MUSIK IRINGAN TARI JEPIN TEMBUNG DI SANGGAR BOUGENVILLE KOTA PONTIANAK - Agusta, Maulingga; Mering, Aloysius; ismunandar, ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe of music accompaniment, the motif of acordion melody, the wasp pattern of beruas and rebana and the implementation at school on Jepin Tembung dance music accompaniment of Sanggar Bougenville Kota Pontianak. The methode used in this research is descrptive explorative methode and using musicology approach.The data in this study is the result of direct observation and interview to the certain informers in the form of accordion melody, pattern of beruas wasp and tambourine. The data are analyzed qualitatively, from the data sources Yuza Chaniago, Juhermi Tahir, Nita Prilian Austin and some artists who has given an active role and know about the music of Jepin dance accompaniment, especially Jepin Tembung dance of Sanggar Bougenville Kota Pontianak. The data is the result of observation, interview and documentation. The result of this study can be concluded that the music accompaniment of Jepin Tembung dance also has the same framer substance with the western music in the literal repeatation, the interval maximize, the tone value maximize and the interval minimize Keywords : Musicology Music Computation Dance of Jepin Tembung Sanggar Bougenville